2020
DOI: 10.1002/ange.202000292
|View full text |Cite
|
Sign up to set email alerts
|

B−B Bond Nucleophilicity in a Tetraaryl μ‐Hydridodiborane(4) Anion

Abstract: The tetraaryl μ‐hydridodiborane(4) anion [2H]− possesses nucleophilic B−B and B−H bonds. Treatment of K[2H] with the electrophilic 9‐H‐9‐borafluorene (HBFlu) furnishes the B3 cluster K[3], with a triangular boron core linked through two BHB two‐electron, three‐center bonds and one electron‐precise B−B bond, reminiscent of the prominent [B3H8]− anion. Upon heating or prolonged stirring at room temperature, K[3] rearranges to a slightly more stable isomer K[3 a]. The reaction of M[2H] (M+=Li+, K+) with MeI or Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…The reaction center of [1aH] À has a B H bond at the end position, the ligand position of [1bH] À has changed, and there is still a hydrogen bridge bond. 49,50 Based on Wagner's experimental results, 30 the cycloaddition mechanisms of [1H] À with CO 2 , iPrNCO, and iPrNC-NiPr are determined. The optimized xyz coordinates of all these stationary points are listed in SI.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The reaction center of [1aH] À has a B H bond at the end position, the ligand position of [1bH] À has changed, and there is still a hydrogen bridge bond. 49,50 Based on Wagner's experimental results, 30 the cycloaddition mechanisms of [1H] À with CO 2 , iPrNCO, and iPrNC-NiPr are determined. The optimized xyz coordinates of all these stationary points are listed in SI.…”
Section: Resultsmentioning
confidence: 99%
“…The former calculation study of M. Wagner et al shows that [1H] − has three isomers: [1H] − , [1aH] − , and [1bH] − (shown in Scheme 2). Among them, [1H] − is the most stable, and the relative energies of [1aH] − and [1bH] − are slightly higher than that of [1H] − ; only 5.1 kcal/mol and 6.6 kcal/mol 49 . [1H] − can be easily converted to [1aH] − and [1bH] − by Wagner–Meerwein rearrangement 28,29 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations